A randomised, single-blind, single-dose, three-arm, parallel-group study in healthy subjects to demonstrate pharmacokinetic equivalence of ABP 501 and adalimumab. Issue 3 (27th July 2016) - Kaur, Primal; Chow, Vincent; Zhang, Nan; Moxness, Michael; Kaliyaperumal, Arunan; Markus, Richard
Abstract : Objective: To demonstrate pharmacokinetic (PK) similarity of biosimilar candidate ABP 501 relative to adalimumab reference product from the USA and European Union (EU) and evaluate safety, tolerability and immunogenicity of ABP 501. Methods: Randomised, single-blind, single-dose, three-arm, parallel-group study; healthy subjects were randomised to receive ABP 501 (n=67), adalimumab (USA) (n=69) or adalimumab (EU) (n=67) 40 mg subcutaneously. Primary end points were area under the serum concentration-time curve from time 0 extrapolated to infinity (AUCinf ) and the maximum observed concentration (Cmax ). Secondary end points included safety and immunogenicity. Results: AUCinf and Cmax were similar across the three groups. Geometrical mean ratio (GMR) of AUCinf was 1.11 between ABP 501 and adalimumab (USA), and 1.04 between ABP 501 and adalimumab (EU). GMR of Cmax was 1.04 between ABP 501 and adalimumab (USA) and 0.96 between ABP 501 and adalimumab (EU). The 90% CIs for the GMRs of AUCinf and Cmax were within the prespecified standard PK equivalence criteria of 0.80 to 1.25. Treatment-related adverse events were mild to moderate and were reported for 35.8%, 24.6% and 41.8% of subjects in the ABP 501, adalimumab (USA) and adalimumab (EU) groups; incidence of antidrug antibodies (ADAbs) was similar among the study groups. Conclusions: Results of this study demonstrated PK similarity of ABP 501 with adalimumab (USA) and adalimumab (EU) after a single 40-mg subcutaneous injection. No new safety signals with ABP 501 were identified. The safety and tolerability of ABP 501 was similar to the reference products, and similar ADAb rates were observed across the three groups. Trial registration number: EudraCT number 2012-000785-37; Results.